Competency Development of Pre-service Teachers in Odisha in preparing English Vocabulary Games - Pradhan, Manoranjan (THE PRIMARY TEACHER, 2016)
The importance of English language is increasing by the day. It is accepted as a global language, link language, language of opportunity, trade and commerce, science and technology, information and news, etc. In our country, too, the importance of English language is widely felt everywhere — educational institutions, government formalities and documentation, judicial activities, etc. Realising its importance, the number of English-medium schools is also increasing across the country. But students’ performance in English language in government elementary schools, especially, in rural areas is not satisfactory. This is evident from several education surveys and reports (ASER, U-DISE, etc). It is seen that even students of Class VIII government schools in rural pockets fail to read textbooks of Class II or III. For this, besides other interventions and initiatives, the empowerment of teachers is needed. The present study is an attempt to develop the competency of pre-service teachers (enrolled in two–year diploma course in elementary education). It focuses on preparing English vocabulary games for enriching the vocabulary stock in elementary school students in a joyful environment. This paper consists of few vocabulary games with its playing principles and rules. The games were developed by teacher−trainees of Pre-service Teacher Training Programme — Diploma in Elementary Education (D.El.Ed). It is believed the games can be played in classroom situation to enhance the students’ word power, develop a positive attitude towards learning English language, do away with fear of the students, as well as, teachers for learning and teaching the language.